2019
DOI: 10.1021/acs.iecr.9b04761
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Preparation of g-C3N4 Porous Nanotubes with Enhanced Photocatalytic Activity by Using Salicylic Acid and Melamine

Abstract: Graphitic carbon nitride (g-C 3 N 4 ) nanotubes were produced by using salicylic acid-mediated melamine successfully. The obtained long g-C 3 N 4 nanotube possesses a large specific surface area and a parallel channel structure. Salicylic acid and its decomposition products present in g-C 3 N 4 influenced its formation process and inhibited the crystal growth of g-C 3 N 4 . A possible mechanism is proposed: Salicylic acid and its decomposition products facilitated the formation of g-C 3 N 4 nanosheet, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…142 The calcination of a mixture of melamine and salicylic acid was found to result in the formation of GCN nanosheets, which then spontaneously scrolled into 4-5 mm long tubes with a diameter of around 60 nm and porous 10 nm thick walls. 144 It was assumed that salicylic acid forms complexes with aminogroups of melamine affecting the polycondensation dynamics and precluding the formation of multi-layer stacked bulk GCN structure. As a result, predominantly few-layer sheets were formed, which tended to coil into tubes to reduce the surface energy.…”
Section: Synthesis Of Gcnts Through Scrolling Of Nano-/ Microsheetsmentioning
confidence: 99%
“…142 The calcination of a mixture of melamine and salicylic acid was found to result in the formation of GCN nanosheets, which then spontaneously scrolled into 4-5 mm long tubes with a diameter of around 60 nm and porous 10 nm thick walls. 144 It was assumed that salicylic acid forms complexes with aminogroups of melamine affecting the polycondensation dynamics and precluding the formation of multi-layer stacked bulk GCN structure. As a result, predominantly few-layer sheets were formed, which tended to coil into tubes to reduce the surface energy.…”
Section: Synthesis Of Gcnts Through Scrolling Of Nano-/ Microsheetsmentioning
confidence: 99%
“…The photocatalytic performance of g-C 3 N 4 could be improved by copolymerizing organic acid (anthroic acid, benzoic acid, and naphthoic acid) with urea due to the fact that the benzenering in the g-C 3 N 4 framework could increase the visible light absorbance (Li et al 2018). Salicylic acid (SA) has a benzene-based structure and was proved to improve photogenerated charge carrier transmission of g-C 3 N 4 nanotubes after the copolymerization with melamine (Jia et al 2019). In previous studies, SA-modi ed g-C 3 N 4 showed excellent performance in the degradation of sulfamethazine and TC (Zhou et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Its outstanding physical and chemical properties and its ability to be formed in several nanostructures (nanosheets, nanotubes, etc.) [ 30 , 31 ] are the reason that g-C 3 N 4 has been widely used in various applications, such as pollutant degradation [ 32 ], CO 2 reduction [ 33 , 34 ], water splitting [ 35 , 36 ], photocatalytic applications [ 31 , 37 , 38 , 39 , 40 ], capacitors [ 41 , 42 ], and solar cells [ 43 , 44 , 45 , 46 , 47 , 48 ]. In particular, integration of graphitic carbon nitride into PSCs has drawn special attention, providing devices with potential low fabrication cost, high chemical stability, and feasibility of structure modification via surface engineering [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%